Interactive network visualization of opioid crisis research: a tool for reinforcing data linkage skills for public health policy researchers - Scrivner, Olga; Nguyen, Thuy; Ginda, Michael; Simon, Kosali; Börner, Katy (Frontiers in Artificial Intelligence, 2024)
Public health policy researchers face a persistent challenge in identifying and integrating relevant data, particularly in the context of the U.S. opioid crisis, where a comprehensive approach is crucial. In order to meet this new workforce demand health policy and health economics programs are increasingly introducing data analysis and data visualization skills. Such skills facilitate data integration and discovery by linking multiple resources. Common linking strategies include individual or aggregate level linking (e.g., patient identifiers) in primary clinical data and conceptual linking (e.g., healthcare workforce, state funding, burnout rates) in secondary data. Often, the combination of primary and secondary datasets is sought, requiring additional skills, for example, understanding metadata and constructing interlinkages. To help improve those skills, we developed a 2-step process using a scoping method to discover data and network visualization to interlink metadata. We show how these new skills enable the discovery of relationships among data sources pertinent to public policy research related to the opioid overdose crisis and facilitate inquiry across heterogeneous data resources. In addition, our interactive network visualization introduces (1) a conceptual approach, drawing from recent systematic review studies and linked by the publications, and (2) an aggregate approach, constructed using publicly available datasets and linked through crosswalks. Finally, these novel metadata visualization techniques can be used as a teaching tool or a discovery method and can also be extended to other public policy domains.